ANTI-MICROBIAL POTENTIAL OF CANNABIS PLANT EXTRACT AGAINST BACTERIA ISOLATED FROM GUT AND MUCUS OF OREOCHROMIS MOSSAMBICUS - RIAZ, Z; KHALID, S; ALI, Q; ASHFAQ, N; Hayat, S; AHMAD, F; HAIDER, MS (Biological and Clinical Sciences Research Journal, 2022)
Cannabis sativa L. is one of the oldest medicinal plants used by human. The plant has also been used for fiber, oil production and simply as additive for food products. Cannabis plant extract may be used for anti-bacterial activity. Bacteria present naturally on the skin, in the gut and in the slime of live fish although. They are not harmful for the fish. But fish get infected with most micro-organisms due to various causes. The goal of this study was to identify the targeted bacteria from mucus and gut of tilapia fish, to study the antimicrobial resistance of isolated bacteria. Thirty samples of Oreochromis mossambicus were collected from Tounsa Head Barrage, Punjab Pakistan. Mucus was collected through spatula. In the laboratory, fish was dissected; gut was removed with the help of a sterile dissecting box. Bacteria were isolated and grown on nutrient agar. E. coli, Staphylococcus spp, Klebsiella spp, B. cereus were isolated from the gut and the mucus while Enterobacter bugandensis was separated from the gut only of the fish. Anti-microbial activity test was done then measure the zone of inhibition in mm. The cannabis showed higher inhibition in growth of E. coli, and Klebseilla spp., while cannabis plant extract showed less inhibition in growth of Staphylococcus spp, Enterobacter bugandensis and B. cereus. It was concluded from our research that the cannabis may be used to develop antibacterial medicines.